2015
DOI: 10.1007/s10461-015-1014-1
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of HIV Risk Behaviors and Trauma Among Forced and Unforced Migrant Populations from Low and Middle-Income Countries: State of the Literature and Future Directions

Abstract: The aim of the current systematic review is to examine the relationship between trauma and HIV risk behaviors among both forced and unforced migrant populations from low and middle income countries (LMIC). We conducted a review of studies published from 1995 to 2014. Data were extracted related to (1) the relationship between trauma and HIV risk behaviors, (2) methodological approach, (3) assessment methods, and (4) differences noted between forced and unforced migrants. A total of 340 records were retrieved w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 55 publications
1
19
0
Order By: Relevance
“…Further, following the disruption of social ties and the consequent stress associated with migration (Michalopoulos, Aifah, & El-Bassel, 2016) (Table 1), arrival communities appear to be strongly determinative risk environments for injection initiation risk among migrants, particularly migrants residing in neighborhoods with above average injecting prevalence resulting from below average socioeconomic indicators (Durrant & Thakker, 2003; Robertson et al, 2012). For example, among Vietnamese women living in a neighborhood in Melbourne, Australia with a disproportionate number of PWID, injection initiation was reported by participants as a way to attain desired social connections following migration (Higgs et al, 2008).…”
Section: Migration Classes and Injection Initiationmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, following the disruption of social ties and the consequent stress associated with migration (Michalopoulos, Aifah, & El-Bassel, 2016) (Table 1), arrival communities appear to be strongly determinative risk environments for injection initiation risk among migrants, particularly migrants residing in neighborhoods with above average injecting prevalence resulting from below average socioeconomic indicators (Durrant & Thakker, 2003; Robertson et al, 2012). For example, among Vietnamese women living in a neighborhood in Melbourne, Australia with a disproportionate number of PWID, injection initiation was reported by participants as a way to attain desired social connections following migration (Higgs et al, 2008).…”
Section: Migration Classes and Injection Initiationmentioning
confidence: 99%
“…So, although epidemics of blood-borne disease have been identified among PWID over the past three decades, mobility is emerging as a driving factor in syndemics of blood-borne disease and IDU (Beyrer et al, 2000; Folch et al, 2016; Rachlis et al, 2007). Notably, the relationship between migration and IDU may be bidirectional, as studies have observed PWID migrating in order to seek addiction treatment, as well as mixing with local PWID populations upon arrival, as has been observed among Puerto Rican migrants in the Northeastern U.S. (Deren et al, 2014; Michalopoulos, Aifah, & El-Bassel, 2016). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Population mobility plays an important role in health, particularly in relation to infectious diseases (Hirsch, 2014; Michalopoulos, Aifah, & El-Bassel, 2016; Rachlis et al, 2007; Weine & Kashuba, 2012). Although there is often a concern that mobile populations can introduce infectious diseases to populations in the settings to which they travel (Grove & Zwi, 2006; Kamper-Jorgensen et al, 2012), they may also be exposed to new or increased risks in these settings compared with their place of origin (Goldenberg, Strathdee, Perez-Rosales, & Sued, 2012; Rachlis et al, 2007; Weine & Kashuba, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Research has indicated that high levels of stress and psychosocial problems (e.g. depression, post-traumatic stress disorder and anxiety) among labor migrants from LMIC may be related to HIV risk behavior (Amirkhanian et al, 2011; Michalopoulos, Aifah & El-Bassel, 2015; Meyer, Robinson, Chhim, & Bass, 2014). In a systematic review of studies in Africa, the Americas, Europe, Southeast Asia and the Western Pacific, Weine and Kashuba (2012), found that difficult and dangerous housing and working conditions, as well as mental health problems were associated with HIV risk among labor migrants.…”
mentioning
confidence: 99%